A Fuzzy Differential Evolution Scheduling Algorithm Based on Grid - Fu Qiao; Guoyin Zhang (Institute of Advanced Engineering and Science, 2012)
Aim at the problem of tasks scheduling problem for grid computing based on fuzzy constraints, propose tasks scheduling model of grid computing about tasks scheduling problem. Using fuzzy AHP(analytic hierarchy process) processes fuzzy constraints weight value. Utilize the merit of differential evolutionary algorithm, that is, the algorithm don’t need objective function is continuous and differentiable. Propose fuzzy differential evolutionary algorithm, the algorithm can process tasks scheduling for grid computing based on fuzzy constraint. In the experiments, compare the proposed algorithm with the existing algorithms. the proposed algorithm is more favorable than the existing algorithm in term of reliability, security and drooped task numbers.